A Colloidal Nanopatterning and Downscaling of a Highly Periodic Au Nanoporous EGFET Biosensor. Issue 4 (1st January 2018) - Purwidyantri, Agnes; Kamajaya, Leonardo; Chen, Ching-Hsiang; Luo, Ji-Dung; Chiou, Chiuan-Chian; Tian, Ya-Chung; Lin, Chan-Yu; Yang, Chia-Ming; Lai, Chao-Sung
Abstract : The nanopattern of highly ordered and uniform Au nanoporous membranes with different sizes and thicknesses and the downscaling approach through the combination of colloidal based nanosphere lithography (NSL) and thermal evaporation was proposed to fabricate an extending-gate field effect transistor (EGFET) membrane. The fabrication involved the use of PS nanospheres templates of 500 nm and 100 nm in diameters and various Au thickness of 10, 25 and 40 nm. Carried out in the detection of Staphylococcus aureus 16S rRNA hybridization test with analytical range of 10 1 –10 6 pM DNA targets, the smaller the Au nanoporous diameter made up by the thicker Au layer produced a gradual improvement in potentiometric study. The Au-nanoporous produced by the thickest Au film at 40 nm and smaller diameter of PS nanospheres (100 nm) demonstrated the most optimum threshold voltage shift and limit of detection (LOD) of ∼1 pM altogether with remarkable specificity in the presence of highly concentrated non-specific DNA of other pathogens. Analytical outcomes point out that smaller, periodic and uniform nanoporous EGFET membrane facilitated the larger hybridization signal due to the higher active surface area enabling the more optimum control of DNA orientation and immobilization.